2018
DOI: 10.1158/2159-8290.cd-17-1033
|View full text |Cite
|
Sign up to set email alerts
|

CD38-Mediated Immunosuppression as a Mechanism of Tumor Cell Escape from PD-1/PD-L1 Blockade

Abstract: Although treatment with immune checkpoint inhibitors provides promising benefit for patients with cancer, optimal use is encumbered by high resistance rates and requires a thorough understanding of resistance mechanisms. We observed that tumors treated with PD-1/PD-L1 blocking antibodies develop resistance through the upregulation of CD38, which is induced by all-trans retinoic acid and IFNβ in the tumor microenvironment. and studies demonstrate that CD38 inhibits CD8 T-cell function via adenosine receptor sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
440
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(457 citation statements)
references
References 50 publications
16
440
0
1
Order By: Relevance
“…Antagonizing A2AR or inhibiting CD73 has synergistic effects against tumors when combined with anti‐PD‐1 . Furthermore, a recent study showed that resistance to PD‐L1 blockade in mouse models of non‐small cell lung cancer was associated with enhanced expression of CD38 by tumor cells and A2AR‐induced immune suppression . Consistent with an important role for CD38 expression in mediating tumor escape, CD38, or A2AR antagonists enhanced the therapeutic effects of anti‐PD‐L1.…”
Section: Targeting the Tumor Microenvironment To Improve Immunotherapiesmentioning
confidence: 90%
“…Antagonizing A2AR or inhibiting CD73 has synergistic effects against tumors when combined with anti‐PD‐1 . Furthermore, a recent study showed that resistance to PD‐L1 blockade in mouse models of non‐small cell lung cancer was associated with enhanced expression of CD38 by tumor cells and A2AR‐induced immune suppression . Consistent with an important role for CD38 expression in mediating tumor escape, CD38, or A2AR antagonists enhanced the therapeutic effects of anti‐PD‐L1.…”
Section: Targeting the Tumor Microenvironment To Improve Immunotherapiesmentioning
confidence: 90%
“…However, checkpoint blockade as the treatment of MSS CRC is unsuccessful. Moreover, although treatment with immune checkpoint inhibitors provides promising benefits for patients with cancer, the optimal use is encumbered by high resistance rates and requires thorough understanding of the resistance mechanisms . Our results showed that CD38 is overexpressed in PD‐1+ T cells from patients with CRC.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, the decreased number of pDC associated with the use of Dara suggests an additional mechanism of action of Dara through pDC depletion. Recently, Chen et al demonstrated that CD38 upregulation in tumors induces resistance to PD‐1/PD‐L1 blocking antibodies and coinhibition of CD38 and PD‐L1 improves antitumor immune response. Several studies have shown that PD‐L1 is expressed on plasma cells but also on DC in the bone marrow, with a various intensity of PDL‐1 expression among patients .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chen et al demonstrated that CD38 upregulation in tumor induces resistance to programmed cell death 1 (PD‐1)/programmed cell death ligand 1 (PD‐L1) blocking antibodies and coinhibition of CD38 and PD‐L1 improves antitumor immune responses. This mechanism of immune resistance caused by CD38 provides an evident rationale to evaluate immunomodulatory effects of CD38 blockade by Dara on the PD‐L1 expressing immune cells.…”
Section: Introductionmentioning
confidence: 99%